Study on technical performance of asphalt surface treatment - Yang, Sen (Journal of physics. Conference series, 2025)
Material, dust content, temperature, water, and other factors were studied in the performance of asphalt surface treatment. Results show that asphalt surface treatment performance varied with material types and temperature. The loss of the aggregate percentage increases with dust content. Precoated aggregate effectively improves the performance of asphalt surface treatment. Temperature has a positive influence on the performance of asphalt surface treatment. The aggregate residual rate of asphalt surface treatment decreased with the increase in immersion time.